2022
DOI: 10.1155/2022/5064494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-Related Protein 1 Is Involved in Mitochondrial Damage, Defective Mitophagy, and NLRP3 Inflammasome Activation Induced by MSU Crystals

Abstract: Excessive generation of reactive oxygen species (ROS) has great impacts on MSU crystal-induced inflammation. Drp1-dependent mitochondrial fission is closely associated with mitochondrial ROS levels. However, whether Drp1 signaling contributes to MSU crystal-induced inflammation remains unclear. Mice bone marrow-derived macrophages (BMDMs) were primed with LPS and then stimulated with MSU suspensions for 12 h. The protein levels associated with mitochondrial dynamics, oxidative stress, and mitophagy were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In order to provide time-resolved data of ASC-speck formation spanning the full duration of speck formation, the number of ASC-GFP-specks in PMA-differentiated and LPS-primed THP-1-ASC-GFP cell populations activated with either ATP, MSU or nigericin was quantified at multiple time points using fluorescence microscopy. The used concentrations of ATP [ 14 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ], MSU [ [31] , [32] , [33] , [34] , [35] , [36] ] and nigericin [ 21 , 22 , 25 , 27 , [37] , [38] , [39] , [40] ] are commonly found in the literature for NLRP3 activation in THP-1 and other cell models. Untreated controls were also imaged to investigate any potential effects of imaging ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to provide time-resolved data of ASC-speck formation spanning the full duration of speck formation, the number of ASC-GFP-specks in PMA-differentiated and LPS-primed THP-1-ASC-GFP cell populations activated with either ATP, MSU or nigericin was quantified at multiple time points using fluorescence microscopy. The used concentrations of ATP [ 14 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ], MSU [ [31] , [32] , [33] , [34] , [35] , [36] ] and nigericin [ 21 , 22 , 25 , 27 , [37] , [38] , [39] , [40] ] are commonly found in the literature for NLRP3 activation in THP-1 and other cell models. Untreated controls were also imaged to investigate any potential effects of imaging ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Azam Ahmadi team's work demonstrates exercise preconditioning (EP) in a short period did not affect Drp1 (Ahmadi et al, 2022), while inhibiting NLRP3 expression. This finding indicates that EP in a short period is required to inhibit NLRP3 inflammasome independently of Drp1; the reduction of NLRP3 can occur through other mechanisms (Jiang et al, 2022).…”
Section: Exercise Improves MI and Inhibits Nlrp3 Inflammasomementioning
confidence: 85%
“…Azam Ahmadi et al, 2022 found HIIT can effectively decrease heart injury and NLRP3 expression in rats with MI. Interestingly, dynamin-related protein 1 (Drp1), an essential mitochondrial fission protein, can activate NLRP3 inflammasome through ROS generation after MI (Ahmadi et al, 2022;Jiang et al, 2022). However, the Azam Ahmadi team's work demonstrates exercise preconditioning (EP) in a short period did not affect Drp1 (Ahmadi et al, 2022), while inhibiting NLRP3 expression.…”
Section: Exercise Improves MI and Inhibits Nlrp3 Inflammasomementioning
confidence: 99%
“…Dysfunctional and damaged mitochondria are a major source of ROS. 50 KAT8 can promote NADPH oxidase (NOX) in RAW 264.7 cells, ultimately leading to the overproduction and accumulation of ROS. 51 Numerous components of the cell can be oxidized by excessive ROS, including DNA, RNA, proteins, and lipids, thereby disturbing multiple biologic events.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional and damaged mitochondria are a major source of ROS 50 . KAT8 can promote NADPH oxidase (NOX) in RAW 264.7 cells, ultimately leading to the overproduction and accumulation of ROS 51 .…”
Section: Discussionmentioning
confidence: 99%